Source-Grid-Load Multi-agent Coordinated Interactive Planning in Power Market Environment - Kang, Yiming; Qin, Wenping; Yao, Hongmin; Xing, Yahong; Hu, Yingying; Jia, Xingping (Dianli Jianshe = Electric Power Construction, 2024)
The emergence of a large number of new agents and power market transactions are crucial characteristics of new power systems. A planning model for source-network-load multiagent coordination and interaction based on game theory is proposed to comprehensively consider the interests of multiple subjects and market factors. First, the market relationship of each agent in the distribution network is analyzed, and the distribution locational marginal price is integrated into the optimal configuration model of the distributed power operators, distribution network operators, and power users. Second, a demand side response model is established based on the power utility function of the user. Third, combined with the game relationship between the three, a source-network-load coordinated interaction model is constructed, and an iterative search method based on the particle swarm optimization algorithm is used to solve it. Finally, the improved IEEE 33-bus system and the actual 9-bus system are used for the example analysis. The results show that considering the interest relationship of each subject in the electricity market environment can slow down the investment of lines and distributed power sources while ensuring the balance of interests among the subjects, which has practical significance.